Blagostanje zaposlenih z obveznostmi oskrbe in nege starejših svojcev - Tement, Sara (Psihološka obzorja (Ljubljana), 2025)
Caring for elderly relatives is an increasing challenge for the working population, and the number of employees who must balance such responsibilities with work is expected to grow. Past research has mainly focused on the negative outcomes of this reconciliation, particularly in terms of individual well-being and health, while overlooking potential positive outcomes, as well as the contextual moderators and mediators that influence these effects. To address this gap, the present review synthesizes the antecedents of physical, social, and psychological well-being from both the work and family domains, as well as the role of personality traits and the sociocultural context. These factors are examined through the lens of Demands-Resources Theory and Ecological Systems Theory. A review of relevant literature identified 22 articles published between 2017 and 2024. The results indicate that demands in both work and personal life are negatively associated with well-being indicators. As expected, resources show a positive association with various aspects of well-being. This article also addresses the specific contexts in which studies were conducted, explores contextual moderators and mediators between these factors and outcomes, and contributes to a broader understanding of the well-being of employees with elder care responsibilities. Finally, the review highlights new opportunities for future research on this growing group within the workforce.
Keywords: duševno blagostanje; employees; informal eldercare; nega in oskrba svojcev; physical well-being; psychological well-being; social well-being; socialno blagostanje; telesno blagostanje; zaposleni